Re-Presenting Rossetti: The Art of Frank Cadogan Cowper - (:unkn) unknown (My University, 2013)
The art of Frank Cadogan Cowper is virtually unknown, yet his paintings attest to a post-modern presence in British art during the rise of High-Modernism. Cowper maintained a 19th-century style during the development of formalism and was not alone. The artist belongs to a wider, loosely formed group of marginal, British painters who drew inspiration from the art of Dante Gabriel Rossetti. Like Rossetti, Cowper was particularly fascinated with the cultural phenomenon of the femme fatale, whose iconography forms a pervasive motif in the artist's oeuvre. Against the wider cultural context, one of the more salient transformations in social stratification during 1890-1914 is the emergence of the New Woman. Encoded in the artistic representations of Cowper is fear, yet fascination with female sexuality; his imagery throws into relief a set of interrelated preoccupations and anxieties, which are part of a larger ideological and artistic structure. This thesis offers the first analysis of Cowper's paintings within England's fin-de-siecle discourses on sexuality and art. Using Royal Academy archival letters written from Cowper to his mother during the early years of his career and through the study of his patrons, I position Cowper's paintings within an interpretive framework. What emerges is an imaginative collision of ironic, irrational, yet traditional and highly decorative imagery, which engages with culture in a distinctive way. Yet, beyond the obvious cultural and artistic implications of Cowper's many paintings, the artist's imagery ultimately opposes the separation of art from life, a central theme of Post-modernity.
Keywords: British; Frank Cadogan Cowper; Magic Realism; Rossetti; Satire; Victorian Art